EVALUATION OF COMMUNITY PARTICIPATION IN COMMUNITY-BASED WATER SUPPLY AND SANITATION PROGRAMS IN KAMPUNG RANTAU JAYA ILIR, CENTRAL LAMPUNG REGENCY - Praja, Tondano Trisna; Rengganis, Dyah Wulan Sumekar; Iryani, Dewi Agustina; Hakim, Lukmanul (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This research is an effort to understand the sustainability issues of the PAMSIMAS (Community-Based Water Supply and Sanitation) program in Rantau Jaya Ilir Village, Central Lampung Regency. Using quantitative and qualitative approaches, this study tried to identify factors that affect the sustainability of the program. In the qualitative approach, researchers explore literature from various sources to explain the factors causing disruption to the PAMSIMAS program theoretically, while in the quantitative approach, data are collected through questionnaires distributed to program beneficiary communities. The results of this study cover several important aspects. First, the PAMSIMAS program in Rantau Jaya Ilir Village provides significant benefits to the community, especially in improving access and quality of clean water. Second, variables such as age, education, income, and length of stay of the community have a significant relationship with the level of participation in the program. Third, SWOT analysis shows that community participation is in quadrant I, which offers opportunities and strengths to improve programs.